New Bouguer Gravity Maps of Venezuela: Representation and Analysis of Free-Air and Bouguer Anomalies with Emphasis on Spectral Analyses and Elastic Thickness - Javier Sanchez-Rojas (International Journal of Geophysics)
A new gravity data compilation for Venezuela was processed and homogenized. Gravity was measured in reference to the International Gravity Standardization Net 1971, and the complete Bouguer anomaly was calculated by using the Geodetic Reference System 1980 and 2.67 Mg/m3. A regional gravity map was computed by removing wavelengths higher than 200 km from the Bouguer anomaly. After the anomaly separation, regional and residual Bouguer gravity fields were then critically discussed in term of the regional tectonic features. Results were compared with the previous geological and tectonic information obtained from former studies. Gravity and topography data in the spectral domain were used to examine the elastic thickness and depths of the structures of the causative measured anomaly. According to the power spectrum analysis results of the gravity data, the averaged Moho depths for the massif, plains, and mountainous areas in Venezuela are 42, 35, and 40 km, respectively. The averaged admittance function computed from the topography and Free-Air anomaly profiles across Mérida Andes showed a good fit for a regional compensation model with an effective elastic thickness of 15 km.